The limited scope of BPK audit and comparison with other supreme audit institutions - Putra, Angga Kiryaditama; Sugimin, Sugimin (Badan Pemeriksa Keuangan Republik Indonesia, 2024)
The role of BPK is to audit state finance management and accountability in all entities that manage state finances freely and independently. However, the BPK's authority to conduct audits of state finances is debatable and limited when some laws and regulations are inconsistent. This study uses legal doctrinal and comparative legal research to explore improvements/harmonization of regulations and comparisons with SAI in other countries regarding the scope of audit that can be carried out to strengthen BPK's authority further. The results of this study indicate that there is still a conflict of norms regarding the scope of BPK's audit, as well as a conflict of interpretation of what it means to audit the management and accountability of state finances in Indonesia. Improving the legal instruments that regulate the scope of BPK audits can avoid conflicting norms and multiple interpretations of legal norms, allowing BPK's role to be more optimal in the future.